The role of the media in security strategies (on the example of Bayelsa State, Nigeria) - Іде Джон Елліот; Оджіакор-Умензе Іфеома; Емека Вільямс Етумну (Cхід)
Mass media as an important element of mass communication influence the formation of public opinion, the perception of security challenges in society. In an effort to fulfil its statutory role of informing the people, the radio media reports security issues so as to arm residents with the needed information. To this end, this study investigated the public perception of radio reports on security issues in Bayelsa State, Nigeria. Agenda-setting and perception theories served as the theoretical foundation of the study. A mixed-methods research design was employed. From the population of 2,277,961, a sample size of 384 was drawn for the study using the Wimmer and Dominick online sample size calculator. Meanwhile, a qualitative population was drawn from security operatives within the state as well as staff from the two private radio stations and two public radio stations.  Questionnaire and interview guide were used as the instruments for data collection. Multistage and purposive sampling techniques were used in the study. Findings revealed that, on average, 62% of Bayelsa residents are exposed to radio reports on security issues within the state to a large extent. The qualitative data revealed similar findings. Further findings revealed that, at an average mean score of 3.1 (N = 377), respondents have positive perceptions. They are of the view that radio reports on security issues are objective. Also, the qualitative findings are in tandem with the quantitative findings.